Spanish notebooks / [by] Ivan Maisky; translated from the Russian by Ruth Kisch. - Kisch, Ruth; Maiskii, I. M. (Ivan Mikhailovich) (1884-1975)
Originally published as Ispanskie tetradi. Moscow, Voen. Izd-vo, 1962.